2015
DOI: 10.1200/jco.2015.62.1888
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Wilms Tumor Treatment and Biology: Progress Through International Collaboration

Abstract: Clinical trials in Wilms tumor (WT) have resulted in overall survival rates of greater than 90%. This achievement is especially remarkable because improvements in disease-specific survival have occurred concurrently with a reduction of therapy for large patient subgroups. However, the outcomes for certain patient subgroups, including those with unfavorable histologic and molecular features, bilateral disease, and recurrent disease, remain well below the benchmark survival rate of 90%. Therapy for WT has been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
328
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 316 publications
(343 citation statements)
references
References 68 publications
5
328
1
9
Order By: Relevance
“…The increasing use of chest CT as routine imaging for staging has resulted in the detection of small pulmonary nodules not visible on chest radiography (CT-only nodules). Similar to the COG protocol, CT-only nodules are included in the definition of lung nodules and treated as metastases in the UMBRELLA protocol if they have a transverse diameter of at least 3 mm (REFS 22,24,25).…”
Section: Cmn Rccmentioning
confidence: 99%
See 2 more Smart Citations
“…The increasing use of chest CT as routine imaging for staging has resulted in the detection of small pulmonary nodules not visible on chest radiography (CT-only nodules). Similar to the COG protocol, CT-only nodules are included in the definition of lung nodules and treated as metastases in the UMBRELLA protocol if they have a transverse diameter of at least 3 mm (REFS 22,24,25).…”
Section: Cmn Rccmentioning
confidence: 99%
“…Results from the COG National Wilms Tumor Study Group (NWTS)-4 and NWTS-5 trials showed that patients with CT-only nodules who were treated with vincristine and actinomycin D plus doxorubicin had superior EFS to those who received vincristine and actinomycin D only, but overall survival was similar in both groups 25 . Including CT-only nodules in the definition of metastatic disease will benefit patients with intermediate-risk or low-risk histology who achieve a rapid complete response of their CT-only nodules.…”
Section: Cmn Rccmentioning
confidence: 99%
See 1 more Smart Citation
“…Dies kann auf ein TDS hinweisen [6]. Die therapeutische Stratifizierung basiert auf der Einteilung in Risikogruppen, die in Abhängigkeit vom Studienprotokoll auf einer Auswahl aus folgenden Faktoren beruht: Alter bei Diagnosestellung, Tumorgröße/-volumen, Histologie, Ansprechen auf Chemotherapie und molekulargenetische Marker (zum Beispiel "loss of heterozygosity" in 1p und 16q) [5,7,8]. Neben der möglichst vollständigen operativen Tumorresektion werden Chemotherapie und Strahlentherapie eingesetzt.…”
Section: Klinische Charakteristikaunclassified
“…[1][2][3][4] However, patients with bilateral Wilms tumor (BWT) have significantly poorer results. On National Wilms Tumor Study 5 (NWTS-5), the four-year EFS estimates for all patients with BWT was 56% (95% CI: 44.8% -66.6%); for patients with favorable histology, focal anaplastic and diffuse anaplastic BWT, four-year estimates were 65% (with retention of heterozygosity at 1p), 76% and 25%, respectively.…”
Section: Introductionmentioning
confidence: 99%